1998
DOI: 10.1071/pp97047
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of root and leaf water status in maize (Zea mays) subjected to mild soil dryness

Abstract: The aim of this work was to test the sensitivity of the water potential (Ψw), osmotic potential (Ψs) and turgor (Ψp) of roots and leaves of maize seedlings (Zea mays L. cv. Carla) subjected to a mild stress in drying soil in a growth chamber. To the best of our knowledge there are no experimental data which describes diurnal courses of Ψw in soil, roots, and leaves and the parallel changes in the osmotic potential (Ψs) and turgor (Ψp) of roots and leaves from plants grown in moist and drying soil. Root and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The enhanced root growth may be able to explore and absorb more water and nutrients from the soil [8,24,46]. The lower shoot DW with N, NP and NPK fertilization may be due to an increase in assimilate allocation to roots for maintaining root growth, for osmotic adjustment and for turgor maintenance [10,25,26]. Similar results were reported by other authors [21,47,48].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The enhanced root growth may be able to explore and absorb more water and nutrients from the soil [8,24,46]. The lower shoot DW with N, NP and NPK fertilization may be due to an increase in assimilate allocation to roots for maintaining root growth, for osmotic adjustment and for turgor maintenance [10,25,26]. Similar results were reported by other authors [21,47,48].…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, the root/shoot ratios were significantly increased with N, NP, PK and NPK supply under drought conditions compared with well-watered conditions (Figure 7). Possibly, with the development of less soil moisture, plants respond to drought by increasing root biomass or a root absorptive surface relative to the shoot biomass [25,26,30]. The enhanced root growth may be able to explore and absorb more water and nutrients from the soil [8,24,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3B and 3C). In fact, the soilplant water potential unbalance just before sunrise is quite common and has been mentioned in several studies (Sellin, 1996;Schmidhalter, 1997;Schmidhalter et al, 1998).…”
Section: ѱX As Water Stress Indicator For Pistachiomentioning
confidence: 99%
“…In this study, measurement of Ѱ s before dawn had showed its limitation even when statistical water stress differences were detected between treatments from the fact that it was not representative of a steady state; the maximum of Ѱ s did not take place only at predawn but a few hours later, when trees were in a rehydration process from stage II to stage III (Figures 4.7B and 4.7C). In fact, the soilplant water potential unbalance just before sunrise is quite common and has been mentioned in several studies (Sellin, 1996;Schmidhalter, 1997;Schmidhalter et al, 1998).…”
Section: ѱ S As Water Stress Indicator For Pistachiomentioning
confidence: 99%